Current Issues Related to Athlete Motivation in the Perspective of Literature Review - Sin, Tjung Hauw; Sari, Suci Nanda; Susanto, Eko (Universitas Muhammadiyah Metro, 2021)
Recent studies on athlete motivation have been widely carried out in the last five years. Almost all studies identify subjects that can influence athlete motivation. The purpose of the study in this article was to obtain significant information related to the research topic